1959
DOI: 10.1113/jphysiol.1959.sp006332
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the phasic and the tonic responses of the anterior byssal retractor muscle of Mytilus

Abstract: Since Winton (1934) first introduced the anterior byssal retractor muscle (ABRM) of Mytilus into muscle physiology, various workers have found that it provides a particularly suitable preparation for use in studying the physiology of lamellibranch muscle. Its virtues are, first, that it is made up of a homogeneous population of muscle fibres, each of which probably extends from one end of the muscle to the other; secondly, that it can easily be isolated intact for experiments in vitro. Various types of stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

1964
1964
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 21 publications
3
80
0
Order By: Relevance
“…The work at the beginning of this third period used recognizably modern techniques and was initially devoted to well defining the contractile responses of the muscles. This work showed that the muscles indeed produce, as a function of stimulation protocol, rapidly or very slowly relaxing contractions; that ACh and serotonin are present in the nerves innervating the muscle; that ACh application induces very slowly relaxing contractions; that serotonin application causes these slow relaxations to become rapid but does not induce contractions when applied alone; and that the nerves innervating the muscle contain both substances (Lowy, 1953(Lowy, , 1954Twarog, 1954Twarog, , 1967aTwarog, , 1968Bandmann and Reichel, 1954;Hoyle and Lowy, 1956;Welsh, 1957;Holgate and Cambridge, 1958;Abbott and Lowy, 1958a,b;Jewell, 1959;Takahashi, 1960;Twarog, 1960a,b;Rudwick, 1961;Baguet et al, 1962;Millman, 1964;Baguet and Gillis, 1964;Bullard, 1967;Hidaka et al, 1967;Leenders, 1967;Salánki and Hiripi, 1970;Twarog and Cole, 1972;Lowy and Vibert, 1972;York and Twarog, 1973;Nagahama et al, 1974;Sugi and Suzuki, 1978;Satchell and Twarog, 1978;Muneoka et al, 1978aMuneoka et al, -c, 1979. The muscle's ability to produce both phasic and tonic contractions thus resulted from it having two innervations, one cholinergic and one serotonergic, with the differing stimulation protocols stimulating either only the cholinergic pathway or stimulating both pathways simultaneously.…”
Section: Unique Properties Due To Acto-myosin Interaction 1: Catchmentioning
confidence: 99%
See 2 more Smart Citations
“…The work at the beginning of this third period used recognizably modern techniques and was initially devoted to well defining the contractile responses of the muscles. This work showed that the muscles indeed produce, as a function of stimulation protocol, rapidly or very slowly relaxing contractions; that ACh and serotonin are present in the nerves innervating the muscle; that ACh application induces very slowly relaxing contractions; that serotonin application causes these slow relaxations to become rapid but does not induce contractions when applied alone; and that the nerves innervating the muscle contain both substances (Lowy, 1953(Lowy, , 1954Twarog, 1954Twarog, , 1967aTwarog, , 1968Bandmann and Reichel, 1954;Hoyle and Lowy, 1956;Welsh, 1957;Holgate and Cambridge, 1958;Abbott and Lowy, 1958a,b;Jewell, 1959;Takahashi, 1960;Twarog, 1960a,b;Rudwick, 1961;Baguet et al, 1962;Millman, 1964;Baguet and Gillis, 1964;Bullard, 1967;Hidaka et al, 1967;Leenders, 1967;Salánki and Hiripi, 1970;Twarog and Cole, 1972;Lowy and Vibert, 1972;York and Twarog, 1973;Nagahama et al, 1974;Sugi and Suzuki, 1978;Satchell and Twarog, 1978;Muneoka et al, 1978aMuneoka et al, -c, 1979. The muscle's ability to produce both phasic and tonic contractions thus resulted from it having two innervations, one cholinergic and one serotonergic, with the differing stimulation protocols stimulating either only the cholinergic pathway or stimulating both pathways simultaneously.…”
Section: Unique Properties Due To Acto-myosin Interaction 1: Catchmentioning
confidence: 99%
“…By this time how nerve activity induces muscle contraction was beginning to be understood, which gave rise to the first of the controversies in this field: were the slow relaxations due to continuous activity in the innervating pathways (the 'tetanic' hypothesis), as had been shown to be the basis of a sustained contraction in isolated crustacean limbs (Barnes, 1930), or to a sustained change intrinsic to the muscle itself (the 'catch' hypothesis) (Lowy, 1953;Jewell, 1959). A series of papers before 1960 showed that in the animal and in some in vitro preparations infrequent electrical events were indeed present in the muscle during catch, supporting the tetanic idea (Lowy, 1954(Lowy, , 1955Hoyle and Lowy, 1956;Abbott and Lowy, 1958a,b).…”
Section: Unique Properties Due To Acto-myosin Interaction 1: Catchmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior byssus retractor muscle was dissected according to the procedure described by Jewel1 [6]. 31P-NMR spectra were recorded from freshly excised and resting muscles: for obtaining relaxed muscles, we left them for several hours in aerated sea water.…”
Section: Methodsmentioning
confidence: 99%
“…In the catch state, intracellular [Ca 2ϩ ] is close to basal concentration (1), and redevelopment of force following unloading of the muscle is absent (2). A hypothesis to explain the long term maintenance of catch force was based on a slowing of cycling of myosin attached to actin when activation waned (see Lowy and Millman (3)).…”
mentioning
confidence: 99%